The role of knowledge management in achieving outstanding university performance (Applied study in the Faculty of Management and Economics / University of Kufa) - حمود سعد علي; جياد علي رزاق; كاظم فايق جواد (Journal of Economics and Administrative Sciences, 2009)
The research aims to determine the role of knowledge management to measure performance on a sample of faculties of Administration and Economics the University of Kufa, and to achieve this goal through a researcher from the theoretical literature and research and studies related to the construction of the scheme shows the hypothetical relationship between the variables, which was adopted by the independent variable knowledge management, distributed four variables are: (knowledge generation, knowledge storage, knowledge dissemination, the application of knowledge), as well as four variables representing the variables adopted for the performance of the university are: (to reduce costs and increase profits, improve quality, scientific research, service of the society). The sample consisted of 36 members of the teaching staff or approximately 10% of the community of the study questionnaire was distributed to seek verification of the apparent sincerity and steadfastness, in accordance with the method of alpha - Kronbach to 0.87. The research data were analyzed using SPSS and the results showed the agreement of all members of the sample survey on the importance of knowledge management in the measurement of university performance, and in light of the results of research by developing a set of recommendations and proposals that are appropriate to the nature of the organization.